Catalogue of family-group names in Cerambycidae (Coleoptera) - Bousquet, Yves; Heffern, Daniel J.; Bouchard, Patrice; Nearns, Eugenio H. (Zootaxa, 2009)
Family-group names proposed for beetles belonging to the family Cerambycidae are catalogued and their availability is determined using the rules of the current International Code of Zoological Nomenclature. A synoptic classification of the family summarizes the validity of the names. Type genera of all family-group names are listed and the type species and stems of genera of available family-group names are included. A new family-group name, Elytracanthinini Bousquet (type genus: Elytracanthina Monn, 2005, a replacement name for Elytracantha Lane, 1955) is proposed for Elytracanthinae Lane, 1955. Ichthyosoma armatum Montrouzier, 1855 is designated as type species of Icthyosoma Boisduval, 1835. Reversal of precedence is used to preserve the validity of the following family-group names: Anaglyptides Lacordaire, 1868 (over Anaglyptisidae Gistel, 1848 [Buprestidae]); Dryobiini Arnett, 1962 (over Dryobiadae Gistel, 1856 [Ptinidae]); Hemilophitae Thomson, 1868 (over Amphionychitae Thomson, 1860) and Hétéropsides Lacordaire, 1869 (over Dichophyiaeidae Gistel, 1848). The following family-group names, although junior synonyms, are preserved as valid until an application is submitted to the International Commission on Zoological Nomenclature; in these cases a reversal of precedence could not be applied: Eurypodini Gahan, 1906 (over Zaracinae Pascoe, 1869); Macronides Lacordaire, 1868 (over Enchapteritae Thomson, 1861); Pyresthides Lacordaire, 1868 (over Pseudolepturitae Thomson, 1861 and Erythrinae Pascoe, 1866) and Stenoderinae Pascoe, 1867 (over Syllitae Thomson, 1864). A total of 238 valid cerambycid family-group names (413 available names) are recognized in the following 13 subfamilies: Vesperinae (1 valid family-group name), Oxypeltinae (1), Disteniinae (4), Anoplodermatinae (3), Philinae (1), Parandrinae (2), Prioninae (24), Spondylidinae (5), Necydalinae (1), Lepturinae (8), Lamiinae (80), Dorcasominae (1), and Cerambycinae (107).